SEMANTIC TRANSFORMATIONS OF PHRASEOLOGICAL WORD-COMBINATIONS IN SPORTS DISCOURSE - Berdysheva,; Murtazina,; Boykova,; Karazhaeva,; Golokova, (Revista Inclusiones, 2020)
The word aggression takes a positive meaning in the public space and has many positive connotations. In this regard, the fact of increasing the positive connotation in the lexical and semantic field of certain phraseological word-combinations related to sports topics becomes particularly interesting. The purpose of the work is to identify semantic transformations of the phraseological word-combinations "sports aggression" and "sports anger" in sports discourse (based on the research of the linguistic consciousness of the youth audience).The intuitive sense of changing the meaning of phraseological word-combination is confirmed by the conducted linguostylistic analysis of media texts and psycholinguistic experiments. Nowadays in Russia, the word aggressor is almost not used, which is due to changes in the socio-cultural situation in the country and the world at the turn of two centuries. The adjective aggressive, on the contrary, is often used, but it has suddenly acquired a positive connotation. It is used in word-combinations, such as aggressive advertising, aggressive music that means proactive, assertive, purposeful, active. The same can be said about naming units of word-combinations related to sports: sports aggression, sports anger. This semantic vector manifests itself in the entire space of linguistic culture. The word aggression in public space is colored in positive shades